Classifier performance during dynamic fine grinding in fluidized bed opposed jet mills - Köninger, Benedikt; Spoetter, Christian; Romeis, Stefan; Weber, Alfred P.; Wirth, Karl-Ernst (Advanced Powder Technology, 2019)
Dry grinding of particles to sizes below 10 µm can be realized in fluidized bed opposed jet mills. In these mills the energy for comminution is supplied by pressurized gas, which is introduced through focused nozzles. The gas transports the material towards an internal classifier, which separates the fines from the coarse material. The fines are discharged whereas the coarse material is recycled. Within this study special attention is paid to separation at the classifying wheel. Limestone batch grinding experiments were performed in a fluidized bed opposed jet mill equipped with on-line and in-line probes: The particle size distributions (PSDs) of the product flow and the solid concentration below the classifier were determined on-line. The flow field around the classifier was recorded by a high-speed camera and off-line measurements of the mill inventory and its PSD were performed. Our measurements reveal that the solid transport from the milling zone to the classifier and the classifier performance strongly depend on solid concentration. Increasing the solid feed concentration or the classifier wheel speed leads to unwanted accumulation of product-sized particles inside the mill. In particular, we find high solid loadings of up to 1.05 g⋅g−1 and strong cluster formation (local zones of high solid concentration) in the vicinity of the classifier blades. Estimated separation efficiency curves of the classifier show a strong “fish-hook effect” which increases with the solid concentration. Our findings are relevant for future process optimization by careful tuning of grinding performance, holdup and classifier speed.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Classification; Fluidized bed opposed jet mill; High-speed imaging; Internal separation curve; Process dynamics